The Maintenance of Cakap Karo in Kelurahan Sempakata Medan - Ingrid Gibretta Khairani Ginting (Linguistic, English Education and Art (LEEA) Journal, 2020)
This research aims at describing the maintenance of Cakap Karo in Kelurahan Sempakata Medan which was focus on Karonese parents’ attitude toward heritage language maintenance for their children and their efforts to help their children maintain Cakap Karo as their heritage language in Kelurahan Sempakata Medan. This research is conducted by using qualitative method. Data were collected from twenty Karonese parents who had a child (or children) between the ages of 6-18 years old in 2019, using the questionnaire and interviews. The result revealed that all the parents in this study had positive attitudes and efforts toward their children’s heritage language maintenance. There are some parents’ effort to enhance children’s Cakap Karo skill that found in this research; communication use Cakap Karo at home, use Karonese books, educational Karonese vocabulary books and Karonese songs, bring to the church of GBKP (Gereja Batak Karo Protestan) and traditional ceremonies, and connect with Karonese relatives and friends in home town using internet. This study confirms that parents’ attitude and efforts play important role in language maintenance. Keywords: Maintenance, Cakap Karo, Parents’ attitude, Heritage Language, Kelurahan Sempakata